Higher serum uric acid levels are associated with an increased risk of carotid atherosclerosis in 67,256 adults - Chen, Renhao; Geng, Yifan; Lin, Mingyi; Qiu, Lei; Ning, Yi; Zhou, Qionggui (Frontiers in Nutrition, 2026)
BackgroundThe association between serum uric acid (SUA) and carotid atherosclerosis (CAS) remains controversial, particularly regarding its independence from traditional risk factors. This cross-sectional study aimed to investigate this relationship and its dose–response pattern in 67,256 adults.MethodsWe conducted a cross-sectional analysis of 67,256 participants who underwent health check-up at Beijing MJ Healthcare Center between 2012 and 2022. Data collected included demographics, physical exams, laboratory tests, and carotid ultrasound. Participants were divided into quartiles based on baseline SUA levels. Multivariate logistic regression analysis was performed with four models to assess the association between SUA and CAS, as well as its subtypes, including increased carotid intima-media thickness (cIMT) and carotid plaque (CP). Additionally, SUA was treated as a continuous variable, and a Restricted Cubic Spline (RCS) model was fitted to explore the dose–response relationship. Subgroup and sensitivity analyses were conducted to examine the heterogeneity and robustness of our findings.ResultsThe prevalence of CAS was 28.8%. Each standard deviation (per-SD) increase in SUA was significantly associated with CAS risk (OR = 1.22, 95% CI: 1.20–1.24, Model 1), (OR = 1.07, 95%CI: 1.04–1.10, Model 4). When SUA was analyzed by quartiles, the Q4 group showed a higher CAS risk (OR = 1.85, 95%CI: 1.76–1.95, Model 1), (OR = 1.19, 95%CI: 1.10–1.28, Model 4). Consistently, across different CAS subtypes, higher levels of SUA were associated with an increased risk of both increased cIMT and CP. The RCS model revealed a linear dose–response relationship in the total population, with CAS risk increasing when SUA exceeded 324 μmol/L. Subgroup analysis demonstrated sex-specific associations: higher SUA (Q4) was significantly linked to CAS in females (OR = 1.34, 95%CI: 1.14–1.58) but not in males (OR = 1.04, 95%CI: 0.92–1.17). There is a linear dose–response relationship for females and a nonlinear trend for males. Both age groups (<60 and ≥60 years) showed increased CAS risk with elevated SUA. Sensitivity analyses excluding individuals with hypertension, diabetes, or dyslipidemia yielded consistent results (per-SD: OR = 1.08, 95%CI: 1.04–1.12; Q4 group: OR = 1.19, 95%CI: 1.06–1.33).ConclusionThe prevalence of CAS was high in the Beijing health check-up population, and high levels of SUA were significantly associated with an increased risk of CAS, particularly in females.